The Effect of Health Consciousness, Environmental Attitudes and Environmental Knowledge on Green Purchase Intention (Case Study on Corkcicle) - Fitriani, Muchbita; Warganegara, Tri Lestira Putri (Future Science / FSH-PH Publications, 2024)
Introduction: Demand for sustainable goods and corporate methods has surged due to growing awareness of environmental and health concerns on a worldwide scale. Consumers are increasingly showing their interest in participating in lifestyles that support health and environmental sustainability. Research on green purchase intentionxis important for further research and analysis. This research aims to test and analyzexthe effect of health consciousness, environmental attitudes, and environmental knowledgexon green purchase intention, using Corkcicle as a case study. Method: This research categorized as quantitative study and will examine the scope ofxthexeffectxof health consciousness, environmentalxattitude, andxenvironmental knowledgexon green purchasingxintention for Corkcicle tumbler products. The population that was the focus of the research was the people of Bandar Lampung and sampling was carried out on 50 respondents using the purposive sampling method. This research employs multiple methods forxdataxanalysis. Result: The results of this research indicate that the three independent variables—environmentalxknowledge, environmental attitudes, and health consciousness—have a positivexeffect onxthe desire to makexgreen purchases. Conclusion: The more likely someone is to intend to buy green goods, the better their level of environmental knowledge, attitudes toward environmental issues, and health awareness.